Impact of national valsartan recalls on Veterans' outcomes - Paige L. Morizio; Sara R. Britnell; Andreina A. Ottman (SAGE Publishing, 2021)
Background and Aims: Chemical impurities discovered in angiotensin receptor blocker (ARB) products in late 2018-2019 resulted in recalls of various products and has likely had downstream effects for patients and prescribers. The purpose of this study is to determine how the valsartan recall impacted clinical endpoints and prescribing of antihypertensives. Methods: This was a retrospective, single-center, cohort study including patients receiving recalled valsartan with essential hypertension who were mailed a recall letter on 12 March 2019. Mean blood pressure endpoints were collected 6 months before (pre-recall) and after the recall letter was mailed (post-recall). Antihypertensive medication changes and titrations were also characterized post-recall. Results: A total of 300 patients meeting eligibility criteria were included. There was no statistically significant difference in mean systolic blood pressure (SBP) or diastolic blood pressure (DBP) when pre- and post-recall blood pressures were compared (SBP: 137.2 mmHg versus 135.8 mmHg, p  = 0.125; DBP: 78.6 mmHg versus 78.5 mmHg, p  = 0.900). In addition, the percentage of patients with controlled blood pressure readings was similar in the pre- and post-recall timeframes (28% versus 27%, p  = 0.72). A total of 33 medication changes involving valsartan occurred, with approximately one-third being changed to another ARB ( n  = 11) or drug class ( n  = 12). In total, 11 valsartan medication changes were specifically documented to be related to the valsartan recall. Conclusion: The results of this study indicate the valsartan recalls that occurred in 2019 did not significantly impact the clinical outcomes of the studied population. Plain Language Summary Impact of a medication recall on Veterans' outcomes Background: Chemical impurities discovered in a class of blood pressure medications known as angiotensin receptor blockers (ARBs) occurred in late 2018-2019. This resulted in recalls of various products and has likely had downstream effects for patients and prescribers. Objective: The purpose of this study is to determine how the recall of valsartan, which is a medication in the ARB class, impacted clinical endpoints and prescribing of medications for blood pressure. Methods: This was a retrospective, single-center, cohort study including patients receiving recalled valsartan with high blood pressure who were mailed a recall letter on 12 March 2019. Blood pressure endpoints were collected 6 months before (pre-recall) and after the recall letter was mailed (post-recall). Medication changes and titrations were also characterized post-recall. Results: Three hundred patients meeting eligibility criteria were included. There was no difference found in systolic blood pressure (SBP) or diastolic blood pressure (DBP) when pre- and post-recall blood pressures were compared (SBP: 137.2 mmHg versus 135.8 mmHg; DBP: 78.6 mmHg versus 78.5 mmHg). In addition, the percent of patients with controlled blood pressure readings was similar in the pre- and post-recall timeframes (28% versus 27%). A total of 33 medication changes involving valsartan occurred, with approximately one-third being changed to another ARB ( n  = 11) or drug class ( n  = 12). Eleven valsartan medication changes were specifically documented to be related to the valsartan recall. Conclusions: The results of this study indicate the valsartan recalls that occurred in 2019 did not significantly impact the clinical outcomes of the studied population.